Influence of temperature and exploitation period on fatigue crack growth parameters in different regions of welded joints (Fracture and Structural Integrity, 2016)
-The influence of exploitation period and temperature on the fatigue crack growth parameters indifferent regions of a welded joint is analysed for new and exploited low-alloyed Cr-Mo steel A-387 Gr. B. Theparent metal is a part of a reactor mantle which was exploited for over 40 years, and recently replaced with newmaterial. Fatigue crack growth parameters, threshold value Kth, coefficient C and exponent m, have beendetermined, both at room and exploitation temperature. Based on testing results, fatigue crack growth resistancein different regions of welded joint is analysed in order to justify the selected welding procedure specification
Keywords: Welded joint; Crack; Yield stress; Tensile strength; Permanent dynamic strength